Pengaruh Kebijakan Pimpinan Bappeda Dan Disiplin Pegawai Terhadap Produktivitas Kerja Pada Badan Perencanaan Pembangunan Penelitian Dan Pengembangan Daerah Kota Banjar - Irman Hermana (Pusat Riset dan Inovasi Nasional, 2023)
The Head of Bappeda with the functions and roles he has is very decisive in directing his employees for the smooth running of their daily tasks. This is also related to the position of the head of Bappeda as a government administrator who is responsible for the implementation of services in the relevant office or institution. However, in the indicators of work targets set, there are still many that have not been realized, this will have a negative impact on the organization, so anticipatory steps are needed to overcome these problems. One of the causes of the decline in work productivity is the leadership policy and the not yet optimal work discipline. The formulation of the problem posed includes: How do BAPPEDA leadership policies affect work productivity at BAPPEDA Banjar City? How does Employee Discipline affect work productivity at BAPPEDA Banjar City? In interaction, what are the BAPPEDA Leadership Policies and employee discipline on work productivity at BAPPEDA Banjar City? The method used is a quantitative method. To analyze it using statistical correlation test data analysis and multiple regression with the SPSS program. The results of the analysis prove that leadership policies have a positive and significant effect on work productivity. This means that the better the leadership policy, the higher work productivity and then work discipline has a positive and significant effect on work productivity. This means that the better the work discipline, the higher the work productivity. Furthermore, leadership policies and work discipline simultaneously have a positive and significant effect on work productivity. This means that if leadership policies and work discipline increase, work productivity also increases. The level of relationship X1 and X2 to Y is included in the strong category.